2023
DOI: 10.3390/ma16041673
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of Ultrafiltration Membranes: Corrosion Fouling Aspect

Abstract: The past decade has seen a rise in the importance of the ultrafiltration (UF) technique in the separation of various complex solutions. However, the fouling phenomenon is the main limitation to faster process development. To the best of the authors’ knowledge, the present paper is the first to aim to identify the role of corrosion fouling in long-term UF. For this purpose, polyvinylidene fluoride (PVDF) and polyethersulfone (PES) membranes were used. The investigations were carried out with the use of both pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The deposit layer on the membrane surface usually improves the separation properties of the UF process [25]. It has been shown that not only the pollutants removed from cars but also the components of the liquids used to wash them cause the fouling phenomenon [28]. It is worth noting that waxes used to polish the car body can also be deposited on the membranes.…”
Section: Membrane Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The deposit layer on the membrane surface usually improves the separation properties of the UF process [25]. It has been shown that not only the pollutants removed from cars but also the components of the liquids used to wash them cause the fouling phenomenon [28]. It is worth noting that waxes used to polish the car body can also be deposited on the membranes.…”
Section: Membrane Performancementioning
confidence: 99%
“…To wash the membranes, a solution of Insect agents was used, which is used in car washes to remove insects. These agents, similar to P3 Ultrasil 11, contain NaOH, EDTA tetrasodium salt, and surfactants [26][27][28]. Its advantage is that, unlike commercial agents used for membrane washing, it is approved for use in car washes.…”
Section: Introductionmentioning
confidence: 99%
“…However, membrane fouling remains a Materials 2023, 16, 3117 2 of 15 major challenge in the application of membrane-based technologies for dairy wastewater treatment [8]. Membrane fouling reduces process performance, shortens membrane lifespan, and increases operational costs [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%